A competitive business model for export-oriented salted egg micro, small, and medium enterprises in the Japanese market - MAHBUBI, AKHMAD; FATONI, AHMAD; ABIMANYU, NABIL MUHAMMAD (Asian Journal of Agriculture, 2025)
Abstract. Mahbubi A, Fatoni A, Abimanyu NM. 2025. A competitive business model for export-oriented salted egg micro, small, and medium enterprises in the Japanese market. Asian J Agric 9: 288-297. Japan offers a promising opportunity for Indonesian salted egg Micro, Small, and Medium Enterprises (MSMEs), given that the price of eggs in Japan is more than double that in the domestic market, and the country ranks as the second-largest consumer of eggs globally. This study seeks to formulate a competitive business model for salted egg MSMEs in the Japanese market. This study employs an exploratory approach, involves 60 participants, and incorporates analyses of comparative and competitive advantages, empathy maps, and business model canvas. This study identifies end users and retailers as primary consumer segments. The value proposition featured eggs with an average weight of 70 g, medium salt content, a slightly paler eggshell, and a vibrant egg yolk. Key activities included 11 operations, particularly on improving the monitoring system. Essential resources comprise cages, salt that meets the Indonesian National Standard (SNI) 01-3556-2000 standards, clean water sources, and processing facilities. The key partners include farmers, testing institutions, and Japanese MSMEs. Channels use direct and indirect exporting. The proposed model is of utmost importance, as it underscores the need importance for fostering collaborative partnerships between supply chain actors. The cost structure delineates the expenses related to cultivation, processing, and delivery. The revenue model is structured around profit-sharing agreements.
Keywords: Business model, comparative advantage, competitive advantage, poultry, salted egg